English as a second language teachers' phenomenon of preseverance in rural Sabah secondary schools - Ameiruel Azwan Ab Aziz (2018)
The purpose of this phenomenological case study was to explore ESL teachers' phenomenon of perseverance through their lived experiences in ten rural Sabah secondary schools. The central research question was "What are the lived experiences of ESL teachers who persevere in rural Sa bah secondary schools?". Sub-questions explored the sources of stress, teachers' sense of self-efficacy and their coping strategies. Methodology utilized a phenomenological case study research design, purposive sampling, data collection primarily through in-depth interviews and observations, and thematic data analysis using Ryan and Bernard's (2000) recommended procedures. The ESL teachers in the study concluded that rural schools do not benefit from conducive environment to support the teaching and learning of English and perceived teaching English in these schools as a stressful task. The facets of rural teaching and learning environment were acknowledged to have significant influences in the formation of teachers' sense of self-efficacy, however, their self-efficacy levels varied based on context-specific basis. Interestingly, the negative descriptions were not considered as sufficient drive for the teachers to depart from rural schools as they have developed a blended concepts of positive emotions as a substantial factor of fuel source to continue serving rural schools. The blended concepts reflecting an emotionteacher- students relationship was placed at the core of their lived experiences as major force for ESL teachers' perseverance. Moreover, four coping strategies remarked as a psychological support to cope with stress were also contributed to teachers' perseverance and longevity in rural schools. The findings of this study could contribute incrementally to the advancement of knowledge on English education by providing insights into the subject and context-specific descriptions especially in supporting perseverance and longevity of ESL teachers in rural schools.